1996
DOI: 10.1093/oxfordjournals.humrep.a019073
|View full text |Cite
|
Sign up to set email alerts
|

Andrology: Fertilizing ability of immotile spermatozoa after intracytoplasmic sperm injection

Abstract: Sometimes spermatozoa from ejaculate, epididymis or testis show a total absence of motility. For some patients, however, very few spermatozoa with very poor motility can be found after several hours of incubation (initially immotile spermatozoa). Other samples show no motility at all even after extended culture (totally immotile spermatozoa). Intracytoplasmic sperm injection (ICSI) is the only method available to select and retrieve a single immotile or initially immotile spermatozoon and inject it into the oo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
70
0
7

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(83 citation statements)
references
References 0 publications
6
70
0
7
Order By: Relevance
“…However, retrospective analysis of the ART outcomes have demonstrated that the fertilization rates, embryo qualities and pregnancy rates are poor when spermatozoa with low motility have been used for fertilization as compared to those with normal motility [14,17,28]. Surprisingly, the fertilization rate and embryo quality could only be marginally improved even after the use of ICSI [28]. These findings are further reconfirmed in our retrospective analysis where couples with oligoasthenozoospermia has poor ART outcome despite the use of ICSI (Table 2).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…However, retrospective analysis of the ART outcomes have demonstrated that the fertilization rates, embryo qualities and pregnancy rates are poor when spermatozoa with low motility have been used for fertilization as compared to those with normal motility [14,17,28]. Surprisingly, the fertilization rate and embryo quality could only be marginally improved even after the use of ICSI [28]. These findings are further reconfirmed in our retrospective analysis where couples with oligoasthenozoospermia has poor ART outcome despite the use of ICSI (Table 2).…”
Section: Discussionsupporting
confidence: 76%
“…ART outcomes have demonstrated that the fertilization rates, embryo qualities and pregnancy rates are poor when spermatozoa with low motility have been used for fertilization as compared to those with normal motility [14,17,28]. A retrospective analysis of the data from our clinic in the last 5 years have reconfirmed the notion that the ART outcome is generally poor in couples with oligoasthenozoospermia despite the use of ICSI (Table 2).…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Before it was possible to directly inject a single spermatozoon into the ooplasm, subzonal injection (SUZI) of numerous sperms was a successful alternative [23,24]. However, SUZI required at least minimal sperm motility in order achieve fertilization.…”
Section: Discussionmentioning
confidence: 99%